The Making of Pedagogy of the Oppressed : Paulo Freire's Approach to Literacy, Training and Adult Education - Jiménez, L. Marcela Gajardo, (Comparative and International Education: The Hispanic Americas ;, 2025)
An unanswered question on the making of Pedagogy of the Oppressed is when, where and how this book was written, edited, and published. The Preface of the original Portuguese handwritten manuscript is dated in Chile by 1967. Some scholars imply that the manuscript was finished sometime in March or April 1969. By then, Freire had left Chile and three of his books had been published by the Institute of Research and Training in Agrarian Reform, ICIRA. Freire himself had already committed the English translation, from the original Portuguese manuscript with Herder & Herder in New York, together with the Spanish translation published by Tierra Nueva in Uruguay. This book explores the ways in which Freire's time and work in Chile proved to be decisive in the making of Pedagogy of the Oppressed , widely considered one of the most important books on critical pedagogy and adult learning and education in the twentieth century. The scope is confined to Paulo Freire's years of political exile in Chile, from late November 1964 to mid-April 1969. It builds upon evidence provided by scholarly research to answer four questions. What did Paulo Freire do during his years of exile in Chile. In which institutional contexts did he develop his pedagogical methods and political ideas? How was his literacy training method and participatory research approach shared throughout Latin America and the rest of the world? To what extent did his exile in Chile influence a paradigm shift in literacy training and adult education?